2018
DOI: 10.1021/acssuschemeng.8b03192
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Approach for Spent V2O5–WO3/TiO2 Catalysts Management: Selective Recovery of Heavy Metal Vanadium and Production of Value-Added WO3–TiO2 Photocatalysts

Abstract: In order to control nitrogen oxides emissions, V2O5–WO3/TiO2 catalysts are widely applied in coal-fired power plants. Consequently, a large number of V2O5–WO3/TiO2 catalysts are spent annually because of their short operating life. Although these spent catalysts contain amounts of heavy metals, they have also been regarded as a potential secondary resource for the recovery of valuable elements titanium, tungsten, and vanadium. Therefore, this study developed an efficient method for selective leaching of heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…The broadband between 925 cm −1 and 1000 cm −1 could be indexed to the overlap of contributions from polymeric vanadate species and both tetrahedrally and octahedrally coordinated polymeric WO x [14,19,32]. In the FTIR spectra (Figure 9), all the samples had a significant vibration band at 1050 cm −1 , which was related to W=O stretches [17]. It also could be found that there was a peak at 1016 cm −1 in the samples with high sulfur content according to XRF and XPS, which might be assigned to the vibration of sulfate [14], and this was consistent with FTIR results showing that there was a vibration band at 1121 cm −1 (Figure 9) [17].…”
Section: Raman Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The broadband between 925 cm −1 and 1000 cm −1 could be indexed to the overlap of contributions from polymeric vanadate species and both tetrahedrally and octahedrally coordinated polymeric WO x [14,19,32]. In the FTIR spectra (Figure 9), all the samples had a significant vibration band at 1050 cm −1 , which was related to W=O stretches [17]. It also could be found that there was a peak at 1016 cm −1 in the samples with high sulfur content according to XRF and XPS, which might be assigned to the vibration of sulfate [14], and this was consistent with FTIR results showing that there was a vibration band at 1121 cm −1 (Figure 9) [17].…”
Section: Raman Analysismentioning
confidence: 99%
“…In the FTIR spectra (Figure 9), all the samples had a significant vibration band at 1050 cm −1 , which was related to W=O stretches [17]. It also could be found that there was a peak at 1016 cm −1 in the samples with high sulfur content according to XRF and XPS, which might be assigned to the vibration of sulfate [14], and this was consistent with FTIR results showing that there was a vibration band at 1121 cm −1 (Figure 9) [17]. As compared with gray samples, the peak between 925 and 1000 cm −1 of yellow samples was broader and higher, meaning that there is much stronger interaction among W, V, and Ti species [20].…”
Section: Raman Analysismentioning
confidence: 99%
“…If the orthogonal experiment had m factors and h levels, k ij was the average value of test indexes in the j level of factor A i , and N was the test index layer matrix, establishing matrix (10):…”
Section: Test Index Layer Matrixmentioning
confidence: 99%
“…The SCR catalysts play an important role in the denitrification process, among which V 2 O 5 -WO 3 (MoO 3 )/TiO 2 catalyst performs a superior catalytic activity, excellent mechanical strength, and perfect anti-inactivation ability [7][8][9]. However, the SCR catalysts have a definite lifetime, which is generally 3-4 years, resulting in being discarded after they lose catalytic activity and fail to be regenerated [10,11]. It is reported that in China, nearly 38,000 tons spent SCR catalyst will be produced every year [12].…”
Section: Introductionmentioning
confidence: 99%
“…CdS [19] 、V 2 O 5 [20] [22] 、TiO 2 /石墨烯 [23] 、TiO 2 /Al 2 O 3 [24] 和 BiFeO 3 [25] 等薄膜催化剂, 对降解有机污染物性能良好。目前 采用金属泡沫镍网负载制备 TiO 2 /WO 3 中存在 Ti、O、W 元素。图 6(b)是样品 Ti2p 的精细 谱图, 两个谱峰 457.9、463.7 eV 分别对应 Ti2p 3/2 和 Ti2p 1/2 的键能, 说明 Ti 是以 Ti 4+ 的形式存在于复 合薄膜中 [29] Nickel foam ln(C 0 /C) = 0.0002t 0.9832 0.0002…”
unclassified